2021
DOI: 10.1007/s42452-021-04623-3
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and isotopic evidence of groundwater salinization processes in the Essaouira region, north-west coast, Morocco

Abstract: The city of Essaouira is located along the north-west coast of Morocco, where groundwater is the main source of drinking, domestic and agricultural water. In recent decades, the salinity of groundwater has increased, which is why geochemical techniques and environmental isotopes have been used to determine the main sources of groundwater recharge and salinization. The hydrochemical study shows that for the years 1995, 2007, 2016 and 2019, the chemical composition of groundwater in the study area consists of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Following the results of the ten years of water quality index, we observed that water quality is deteriorating, particularly on the coast of the aquifers near the Atlantic ocean. The excessive fertilizer used in agriculture seeps into groundwater because the soil surface is close to the water table [10,26]. Therefore, as the hydraulic conductivity is critical, this region is susceptible; another reason is several tourist activities since there is no sanitation network or a water treatment station that generates wastewater infiltration directly onto the water table.…”
Section: Water Quality Index (Wqi) Calculatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the results of the ten years of water quality index, we observed that water quality is deteriorating, particularly on the coast of the aquifers near the Atlantic ocean. The excessive fertilizer used in agriculture seeps into groundwater because the soil surface is close to the water table [10,26]. Therefore, as the hydraulic conductivity is critical, this region is susceptible; another reason is several tourist activities since there is no sanitation network or a water treatment station that generates wastewater infiltration directly onto the water table.…”
Section: Water Quality Index (Wqi) Calculatedmentioning
confidence: 99%
“…Isotopic analysis is a useful tool for deciphering the mechanisms that drive an aquifer system's hydrogeological and hydrochemical evolution [26,79,80]. Stable isotopes of oxygen (δ 18 O) and hydrogen (δ 2 H) are thought to be transported conservatively in shallow aquifers, according to Kim [81].…”
Section: Water Stable Isotopes (δ 2 H-δ 18 O)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered the most critical and apparent phenomenon that challenges future water use and decreases water quality. Because it limits the amount of water used for agriculture and urban water supply [18][19][20][21][22][23], groundwater salinization is critical to the resilience and sustainability of coastal. Increasing total dissolved solids (TDS) or chloride (Cl − ) content signifies salinization [24].…”
Section: Introductionmentioning
confidence: 99%